Dermatophytosis Caused by Microsporum canis in a Free-Living Maned Wolf (Chrysocyon brachyurus). - Pereira, Keylla Helena Nobre Pacífico; Oliveira, Elton Luís Ritir; Gonçalves, Raphael Augusto Baldissera; Rolim, Luna Scarpari; Neto, Ramiro das Neves Dias; Castilho, Maíra Sales; Teixeira, Carlos Roberto; Rahal, Sheila Canavese (Acta Scientiae Veterinariae, 2018)
Background: Chrysocyon brachyurus is a South American wild canid considered a species near threatened by the International Union for Conservation of Nature and is classified as vulnerable in the National List of Endangered Species. With the increase of the contact between domestic animals, human population and wild animals, there was a greater exposure of the maned wolf to pathogens. Due to the importance of its conservation, the knowledge of emerging infectious diseases that affect this species becomes essential. This report aims to describe the first diagnosed case of dermatophytosis caused by Microsporum canis in a maned wolf. Case: A free-living female maned wolf (Chrysocyon brachyurus), approximately 60 days old, was rescued with presence of alopecia, non-pruritic lesions, one of circular shape located in the nasal plane and the other with signs of scaling and crusts in the region of the left pina. The animal was active, in good general condition and without other significant changes to clinical examination. Skin scraping was performed for mycological culture of both lesions. Fungal growth on Sabouraud’s agar identified Microsporum canis. Topical therapy with ketoconazole ointment and cleaning of lesions with 0.2% chlorhexidine was instituted. After 20 days of treatment, remission of clinical signs and repilation of affected areas were observed. New mycological cultures of both areas were carried out, which were negative for Microsporum canis. Discussion: Although Microsporum canis is described as causing dermatophytosis in several animal species, it has apparently not yet been reported in maned wolves. Microsporum canis is one of the most isolated zoophilic dermatophytes in domestic cats and is also cited in reports of symptomatic wild felids, such as tigers, in which it has been identified as either the only agent of infection or in association with Trichophyton mentagrophytes. The occurrence is also high in domestic dogs. In the wild canids, Microsporum gypseum has been described in the gray wolf, Trichophyton mentagrophytes in wild foxes, and Microsporum canis in red fox, among others. The finding of zoophilic and geophilic dermatophyte fungi in healthy, free-living and captive wild animals confirms their role as carriers, probable reservoirs and disseminators of these organisms in the environment, and the potential risk they represent as causes of zoonoses. Zoophilic dermatophytes are usually transmitted by contact between individuals and contaminated fomites. In the case of M. canis in the red fox the contact was an asymptomatic domestic cat. In the present case the transmission was not determined, since the animal was rescued from the wild. Regarding the age group, young animals are more susceptible to dermatophytes than adults, probably related to the greater immunity of adults due to previous contacts or even the immaturity of the immune system of the young. The dermatophytosis diagnosis is generally based on anamnesis, physical examination of the lesion, Wood’s lamp examination, microscopic skin scraping, fungal culture, or even histology and PCR tests. In the present case, the final diagnosis was based upon by fungal culture in Sabouraud agar, which allowed to identify the dermatophyte species and, thus, the possible source of infection. Dermatophyte infections can be treated with systemic or topical antifungal medications. Because it was a young animal, it was chosen in the present case only for topical use, which proved to be adequate, probably due to the action of the drug in the areas of alopecia skin and the improvement of the systemic condition of the animal. Knowing that the maned wolf is considered as a vulnerable species, it is important to know the diseases that affect this species, in order to carry out, when necessary, disease monitoring programs, preventive and therapies, which is essential for its preservation. Keywords: wild animal, disease, skin, dermatophyte.